2002
DOI: 10.1002/pd.363
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethnic origin on nuchal translucency at 10–14 weeks of gestation

Abstract: Although there were statistically significant differences in NT measurements between different ethnic groups, it was clinically insignificant, as reflected by similar screen-positive rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 16 publications
3
26
0
1
Order By: Relevance
“…The 95th percentile NT thickness at a CRL between 75 and <85 mm (2.10 mm) was thinner than the accepted fixed cut-off point (≥2.5 mm). Several studies have reported significant differences in NT thickness measurements among ethnic groups [6,7,8]; however, this was clinically insignificant, as only a small proportion of DS fetuses had an NT thickness at 95th percentile values. A reason for the differences between our study and these earlier ones could be that to acquire the NT measurement, we used the average from three measurements instead of the largest measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 95th percentile NT thickness at a CRL between 75 and <85 mm (2.10 mm) was thinner than the accepted fixed cut-off point (≥2.5 mm). Several studies have reported significant differences in NT thickness measurements among ethnic groups [6,7,8]; however, this was clinically insignificant, as only a small proportion of DS fetuses had an NT thickness at 95th percentile values. A reason for the differences between our study and these earlier ones could be that to acquire the NT measurement, we used the average from three measurements instead of the largest measurement.…”
Section: Discussionmentioning
confidence: 99%
“…This variation could be explained by several factors such as study design, NT cut-off value, gestational age at measurement, selection bias, verification bias, and operator’s experience. Recent studies [6,7,8] have also suggested that there may be significant differences in NT measurements among fetuses of different ethnic origins. This finding may have a potential impact on the screening efficacy of NT, suggesting that, in screening for chromosomal defects, the use of a single cut-off value for fetal NT may be inappropriate [9].…”
Section: Introductionmentioning
confidence: 99%
“…Within a few years, the Danish Fetal Database, which started to collect data on all Danish pregnancies from January 1, 2008, will allow further investigations on the topic [16] . Maternal ethnic origin is known to affect NT [17][18][19] , but we did not adjust for this factor, since the Danish population is mainly Caucasian [20] and only Danish-speaking women were invited to participate in the study (approximately 96% of the participants in the study were Caucasian). In addition, Spencer et al [19] found that average weight and frequency of smokers differed between ethnic groups, and concluded that this may contribute to the observed association between ethnicity and NT.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known the need to correct biochemical markers, such as the free fraction of β-HCG and pregnancyassociated plasma protein-A (PAPP-A), in addition to ultrasound markers, like NT measurement in the first trimester for Down syndrome, in different ethnical groups [3].…”
Section: Introductionmentioning
confidence: 99%